2016
DOI: 10.1038/srep29990
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and γδ T Cells are the main Producers of IL-22 and IL-17A in Lymphocytes from Mycobacterium bovis-infected Cattle

Abstract: Gene transcription studies have identified dual roles for the cytokines IL-17A and IL-22 in bovine tuberculosis, where they show potential as both predictors of vaccine success and correlates of infection. To allow for a detailed investigation of the cell populations responsible for production of these cytokines, we have utilised a novel bovine IL-22 specific recombinant antibody for flow cytometry. Bovine tuberculin (PPDB) induced greater IL-22 and IL-17A production in Mycobacterium bovis (M. bovis)-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 42 publications
5
35
0
1
Order By: Relevance
“…In agreement, Steinbach et al recently described bovine γδ T cells from the periphery as being major producers of IL-22 during infection with M. bovis [43]. Consistent with these previous reports, we measured significant expression of IL-22 in our γδ T cell/macrophage co-cultures; in contrast, however, we observed no expression of IL-22 by γδ T cell within late-stage M. bovis granulomas.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement, Steinbach et al recently described bovine γδ T cells from the periphery as being major producers of IL-22 during infection with M. bovis [43]. Consistent with these previous reports, we measured significant expression of IL-22 in our γδ T cell/macrophage co-cultures; in contrast, however, we observed no expression of IL-22 by γδ T cell within late-stage M. bovis granulomas.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with these previous reports, we measured significant expression of IL-22 in our γδ T cell/macrophage co-cultures; in contrast, however, we observed no expression of IL-22 by γδ T cell within late-stage M. bovis granulomas. This is in agreement with Aranday-Cortes et al , who observed a decrease in IL-22 levels by qPCR in late-stage granulomas from M. bovis -infected cattle [43, 44]. Similarly, Palmer et al observed very low levels of expression of IL-22 by RNAScope in any stage of lesion collected at 150 days post M. bovis infection [63].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…IL-17A is induced in early phases of M. tuberculosis infection14 and contributes to the recruitment of neutrophils1718. Human and animal vaccination studies with M. bovis bacille Calmette-Guérin (BCG) show increased IL-17A responses181920, but specific T cell frequency and cytokine expression profile did not correlate with protection against tuberculosis after BCG vaccination21. The IL-17 pathway seems to be dispensable for low dose M. tuberculosis host resistance1213, while control of a higher inoculum of M. tuberculosis H37Rv1011 or of the hypervirulent M. tuberculosis strain HN878 appears to induce an IL-17A-dependent inflammation, as recently described12.…”
mentioning
confidence: 99%
“…Indeed, enhanced IL-22 and IL-17A mRNA expression in M. bovis-infected cattle following elicitation with BPPD has also been reported [82] thus proposing that evaluation of these cytokines could be useful biomarkers in bovine infection. To investigate the precise cell populations involved in production of these cytokines, Steinbach et al [83] [74,79]. These observations might be useful for further understanding the immunopathology of bovine TB and to produce more accurate immunodiagnostic reagents.…”
Section: Immunological Correlates Of Protection Studies In Cattlementioning
confidence: 99%